Cypher and Enigma Homolog Protein Are Essential for Cardiac Development and Embryonic Survival. Issue 5 (May 2015) - Mu, Yongxin; Jing, Ran; Peter, Angela K.; Lange, Stephan; Lin, Lizhu; Zhang, Jianlin; Ouyang, Kunfu; Fang, Xi; Veevers, Jennifer; Zhou, Xinmin; Evans, Sylvia M.; Cheng, Hongqiang; et al.
Abstract : Background: The striated muscle Z‐line, a multiprotein complex at the boundary between sarcomeres, plays an integral role in maintaining striated muscle structure and function. Multiple Z‐line‐associated proteins have been identified and shown to play an increasingly important role in the pathogenesis of human cardiomyopathy. Cypher and its close homologue, Enigma homolog protein (ENH), are 2 Z‐line proteins previously shown to be individually essential for maintenance of postnatal cardiac function and stability of the Z‐line during muscle contraction, but dispensable for cardiac myofibrillogenesis and development. Methods and Results: The current studies were designed to test whether Cypher and ENH play redundant roles during embryonic development. Here, we demonstrated that mice lacking both ENH and Cypher exhibited embryonic lethality and growth retardation. Lethality in double knockout embryos was associated with cardiac dilation and abnormal Z‐line structure. In addition, when ENH was ablated in conjunction with selective ablation of either Cypher short isoforms (CypherS), or Cypher long isoforms (CypherL), only the latter resulted in embryonic lethality. Conclusions: Cypher and ENH redundantly play an essential role in sustaining Z‐line structure from the earliest stages of cardiac function, and are redundantly required to maintain normal embryonic heart function and embryonic viability.